2020
DOI: 10.1080/13683500.2020.1800601
|View full text |Cite
|
Sign up to set email alerts
|

How corporate social responsibility contributes to strengthening brand loyalty, hotel positioning and intention to revisit?

Abstract: This study aims to investigate if the visitors' perception of corporate social responsibility influences both hotel brand positioning and intention to revisit. Furthermore, it examines the indirect impact of corporate social responsibility on hotel brand positioning and intention to revisit through other major factors (identification, satisfaction, and loyalty). In total, 348 valid questionnaires were collected from customers reserved a hotel room in the UK within the last six months at the time of this invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
77
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(81 citation statements)
references
References 109 publications
(113 reference statements)
1
77
1
2
Order By: Relevance
“…Restaurants are favorably evaluated by customers if it is positively linked up by any CSR activities. Demonstrating a socially responsible behavior toward society increases the customer satisfaction and loyalty and ultimately influences the brand loyalty [14]. Numerous studies have examined the relation of brand trust with brand loyalty [15] even though the role of social trust on customer routine dealings and its ultimate effect on brand loyalty have not yet been explored.…”
Section: Introductionmentioning
confidence: 99%
“…Restaurants are favorably evaluated by customers if it is positively linked up by any CSR activities. Demonstrating a socially responsible behavior toward society increases the customer satisfaction and loyalty and ultimately influences the brand loyalty [14]. Numerous studies have examined the relation of brand trust with brand loyalty [15] even though the role of social trust on customer routine dealings and its ultimate effect on brand loyalty have not yet been explored.…”
Section: Introductionmentioning
confidence: 99%
“…Ultimately, in the long run, all these capabilities will thus lead to enhanced customer loyalty. Therefore, companies should strive for acknowledging the global shift toward communication and implementation of corporate social responsibility (Akbari et al, 2021; Chang & Lee, 2020). These directions are primarily important for less developed countries, where the novelty of corporate social responsibility is not penetrated yet in the decision making process of customers.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, depending upon the comparative shortage of accessible integrating research, the present study reacts toward the various research calls to discover the intervening components that help in identifying, how the customer loyalty is affected by the perception of CSR in the hoteling industry. For this purpose, the intrinsic significance of the CSR seems to be barely tested, but there exists a need to justify firm’s investment in CSR and then to understand its possible positive results for companies still remain an untapped niche (Akbari et al, 2021; Jalilvand et al, 2017b; Liu et al, 2019). To the best of our information, past experimental research in the hoteling industry, have not considered identified mediating variables into the model to clarify the effect of CSR on the customer’s loyalty.…”
Section: Introductionmentioning
confidence: 99%
“…When consumers want to buy a product and a brand name, it reflects a higher brand positioning. If a product has greater brand positioning, customer satisfaction, brand awareness, brand loyalty and the intention of purchase can be influence (Akbari et al, 2020).…”
Section: Brand Awarenessmentioning
confidence: 99%